2004
DOI: 10.1246/bcsj.77.1415
|View full text |Cite
|
Sign up to set email alerts
|

New Large Refractive-Index Change Materials: Synthesis and Photochemical Valence Isomerization of the Calixarene Derivatives Containing Norbornadiene Moieties

Abstract: We have examined the synthesis of cyclic oligomers with pendant norbornadiene (NBD) moieties based on the calixarenes [p-tert-butylcalix[8]arene (BCA), p-methylcalix[6]arene (MCA), calix[4]resorcinarene (CRA), 2,8,14,20-tetradecylcalix[4]resorcinarene (CRA10), and 2,8,14,20-tetrakis(p-hydroxyphenyl)calix[4]resorcinarene (CRAph)]. The photochemical valence isomerization of the obtained calixarene derivatives containing NBD moieties proceeded very smoothly to afford the corresponding quadricyclane (QC) moieties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…1,1¢,1¢¢-Tris(4-glycidyloxyphenyl)methane (TGOPM) was prepared according to an established method. 13 Unless otherwise stated, reagents were purchased from commercial suppliers and used without any further purification.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,1¢,1¢¢-Tris(4-glycidyloxyphenyl)methane (TGOPM) was prepared according to an established method. 13 Unless otherwise stated, reagents were purchased from commercial suppliers and used without any further purification.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…The Dn D 's are dependent on the change of molar refraction (R) and density (r) before and after photoirradiation. 13 The difference of Dn D of HBP c -EPOX and HBP c -OX could be explained by the size of cyclic ether and the efficiency of photo-curing. The high reactivity and compact structure of glycidyl lead to higher crosslinking density, and as a consequence, HBP c -EPOX shows larger Dn D than HBP c -OX.…”
Section: Synthesis Of Hyperbranched Fluorinated Polymers M Miyasaka Ementioning
confidence: 99%
“…From this viewpoint, we designed calixarene derivatives with pendant epoxy groups, and examined the reaction of the resulting calixarene derivatives and 3-phenyl-2,5-norbornadiene-2-carboxylic acid to obtain the corresponding calixarene derivatives with NBD moieties containing pendant hydroxyl groups (Scheme 4). 37 The synthesized calixarene derivatives BCA-NBD, MCA-NBD, CRA-NBD, CRA 10 -NBD, CRA(OH)-NBD were soluble in common organic solvents and had good film-forming properties. The photochemical valence isomerization of these calixarene derivatives with pendant NBD was examined in thin films.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…[1][2][3] Recently, much attention has been devoted to the photochemical control of refractive indices for polymer films, owing to their potential in optical network technology. 3 Although there are extensive studies directed toward a photoinduced decrease in refractive indices for polymer films, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] only a few attempts have been made to enhance the refractive index through photochemical transformations. 12,[20][21][22][23][24][25] For example, Langer et al 21 reported that irradiation of a polymerbearing thiocyanate pendants enhanced the refractive index (n) of the polymer by 0.031.…”
Section: Introductionmentioning
confidence: 99%